ICT-Based Teaching Aids to Enhance English Language Proficiency of Indian Engineering Students - Deepa, R.; Rehena, Sk; Padma, A. Neeraja; Padmalatha, M. K.; Zayed, Enas Kamal; Sathikumari, Meera Karthikeyan Nair; Jamal, Afsha; Saba, Naheed (Theory and practice in language studies, 2024)
Technology has provided access to a wide variety of teaching tools, including digital tools like Google Classroom, Quizlet, Zoom, Kahoot, and Nearpod, as well as older technology like radio, television, video, and computers for those who are both teaching and learning the English language. Even before personal computers first became a common household item in the 1990s, many people believed they would revolutionize education, and using computer-based instruction and learning for the study of languages was no exception. Nevertheless, ICT-based English language learning has only recently become available in India. Technology is currently used in many educational institutions to teach subjects like languages. Consequently, technology in general and information and communication technology (ICT) in particular have made it possible for everyone around the globe to learn for themselves. Therefore, the focus of the researchers nowadays is on utilizing particular ICT-based instructional materials to improve the English language skills of engineering students from rural backgrounds. In the modern day, obtaining a job no longer solely depends on subject-matter expertise. Without a doubt, Rural Background Engineering (RBE) students must be skilled communicators in English these days in order to find employment. This paper focuses on the effective use of technology to enhance Indian RBE students English language instruction within a result-focused context. Therefore, integrating technology into language instruction offers clear benefits that pertain to both language education and preparing pupils for today’s information culture.digital tools